THE IMPACT OF MARKETING INNOVATIONS ON COMPETITIVENESS - Melibаevа Gulxоn Nаzrullаevnа (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article provide the interplay between marketing innovations and competitiveness among firms operating in international markets through local resellers. It emphasizes the importance of collaboration between buyers and sellers in fostering both radical and incremental marketing innovations. By applying complexity theory, the research highlights how strong buyer-seller relationships can enhance a firm’s capacity for innovation and overall competitive advantage. However, the study’s limitations, including its focus on a single industry and geographical context, suggest the need for further research across diverse industries and cultures to fully understand the dynamics of marketing innovations and their impact on competitiveness.